2023
DOI: 10.1002/ente.202201287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electron–Electron Interaction in Charge Transport Calculations through Transition Metal Dichalcogenides Heterojunctions

Abstract: 2D materials have raised a lot of interest in the last decades, due to their novel and diverse properties, particularly for energy technology applications where materials such as molybdenum disulfide are known for their outstanding catalytic ability. While intensive research is devoted to 2D transition metal dichalcogenide (TMDCs) semiconductor characterization, comprehensive understanding of metal/semiconductor heterojunctions is still lacking especially for junctions containing 2D metallic monolayers other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…The trends in charge transport probability and transmission coefficient were found to be similar for CT from either the VB or the CB. Ben-Melech Stan et al recently published an article in which the impact of charge scattering on the charge transport mechanism was considered [113]. The authors reported the charge transport of two electrons through 2D transition metal dichalcogenide heterojunctions (TMDCs) using wave-packet propagation.…”
Section: Charge Transport Via Interfacesmentioning
confidence: 99%
“…The trends in charge transport probability and transmission coefficient were found to be similar for CT from either the VB or the CB. Ben-Melech Stan et al recently published an article in which the impact of charge scattering on the charge transport mechanism was considered [113]. The authors reported the charge transport of two electrons through 2D transition metal dichalcogenide heterojunctions (TMDCs) using wave-packet propagation.…”
Section: Charge Transport Via Interfacesmentioning
confidence: 99%